Contaminação das águas por resíduos de medicamentos: Ênfase ao cloridrato de fluoxetina - Borrely, Sueli Ivone; Caminada, Suzete Maria L.; Ponezi, Alexandre Nunes; Santos, Dymes Rafael dos; Silva, Vanessa H. Ogihara [UNESP] (My University, 2012)
The objective of this paper was to review data on residues of medical products in aquatic environments and at wastewater treatment plants. Secondarily the paper presents a discussion about the need for a good management of drugs residues and effluents generated by this sector. Bringing the evidences of environmental possible damages reported by ecotoxicity data on the effects of fluoxetine to Vibrio fischeri and H. azteca, aquatic organisms daily exposed to environmental contaminants. From the results we observed that 0.3 mg.l-1 of fluoxetine hidrochloride induced lethality to H. azteca and 30 mg.l-1 reduced the luminescence of Vibrio fischeri. This assay evidenced higher toxicity when we used the generic product.
Water contamination by drugs residues, with an emphasis in fluoxetine chloridrate
Keywords: Fluoxetine; Pharmaceutical Preparations; Water